A Review On Artificial Intelligence For Thyroid Nodule Ultrasound (Journal of Pharmaceutical Negative Results, 2022)
Ultrasound is a versatile green imaging modality that is rapidly gaining traction as a first-line imaging tool in a variety of clinical settings, thanks to the ongoing development of sophisticated ultrasonic technology and the well-established Ultrasound-based digital health system. Thyroid nodules are tumours that are mostly benign, but can can be malignant and invasive malignancies. These tumours are curable and become more common as people get older. The size and ultrasound features are used to determine whether or not an ultrasonography-guided biopsy should be performed. The American Thyroid Association's thyroid nodule recommendations count the number of benign or suspicious ultrasonography findings before recommending biopsy or observation depending on the size of the nodule.